Full genomic sequence of the HLA‐DQB1*04:51 allele identified by next‐generation sequencing. (19th August 2021) - Liacini, Abdelhamid; Morris, Thomas; AlZahrani, Saber; Mathew, Leena; Geier, Steven
Abstract : Full‐length sequence of HLA‐DQB1*04:51 covers the 5′‐untranslated region (UTR), all introns and exons and the 3′‐UTR.